#TITLE_ALTERNATIVE# - REZKY NOFAN ( 15108071 ); Pembimbing : Dr. Ir. Kosasih Prijatna, M.Sc.,
A guna lahan / tutupan lahan is part of the ekoregion is very susceptible to external interference in both human social and economic needs as well as of nature. For an estimate of what the vulnerability of guna lahan / tutupan lahan, the experts make a value by looking at the size of the geometric shape of an ecosystem are called shape index.To calculate the index value of the shape required amount of area and perimeter of each tutupan lahan per ekoregion. Because the shape index values obtained by the circumference divided by two times which have extensive root multiplied by the value of π (227).The results of the calculation of this value is a map of the distribution of shape index values for each tutupan lahan per ekoregion. There are 13 maps in accordance with the number of tutupan lahan in the island of Java.